математика

Решить уравнение: 2(x²-7)²-7(x²-7)(x²+1)+3(x²+1)²=0

Оставить ответ
1

Ответ №1

x^2+1>0
делим обе части на (x^2+1)^2

2(\frac{x^2-7}{x^2+1})^2-7\frac{x^2-7}{x^2+1}+3=0
делаем замену
\frac{x^2-7}{x^2+1}=t
2t^2-7t+3=0
D=(-7)^2-4*2*3=49-24=25=5^2
t_1=\frac{7-5}{2*2}=0.5
t_2=\frac{7+5}{2*2}=3

возвращаемся к замене
t=0.5
\frac{x^2-7}{x^2+1}=0.5
x^2-7=0.5x^2+0.5
0.5x^2=7.5
x^2=7.5:0.5
x^2=15
x_1=\sqrt{15}; x_2=-\sqrt{15}

t=3;
\frac{x^2-7}{x^2+1}=3
3x^2+3=x^2-7
2x^2=-10
решений нет
ответ: -\sqrt{15}; \sqrt{15}

Знаете ответ?